Female Leuciscus lepidus May Be a New Alternative for Fish Oil Supplements - Ozlem Cakmak; Aynur Altuntas; Veli Ugurcu; Hacı Kemal Erdemli; Sumeyya Akyol (Journal of Chemistry)
The proximate composition of male and female Leuciscus lepidus in Beyşehir Lake was investigated. The fatty acid profiles of total lipid, phospholipid, and triacylglycerol in muscle and liver of male and female L. lepidus were evaluated by gas chromatography. Proximate analyses showed that meat of male and female L. lepidus had 15.13 ± 0.04 and 18.75 ± 0.11% fat, 20.42 ± 0.45 and 22.21 ± 0.56% protein, 65.47 ± 1.37 and 61.28 ± 1.03% moisture, and 1.51 ± 0.05 and 1.50 ± 0.03% ash, respectively. The percentage of total saturated fatty acids was higher in liver than in muscle, whereas the total polyunsaturated fatty acid (PUFA) content was the lowest in all fatty acid profiles. The phospholipids contained more PUFAs than triacylglycerol. Analysis of variance indicated significant differences (P<0.05) between male (47.51%) and female (49.98%) muscle PUFAs in total lipid. The proportion of omega 3 (ω3) to omega 6 (ω6) fatty acids of total lipid was 3.15 in male and 3.68 in female. The ratio is an important indicator for comparing the value of fish oil. Therefore, it was concluded that L. lepidus was considered to be a high quality product for healthy food choice. Additionally, female L. lepidus may especially be used to produce fish oil supplements from freshwater fish combined with vegetable oils.